Amino acids at the N- and C-termini of human glutamate carboxypeptidase II are required for enzymatic activity and proper folding - Barinka, Cyril; Mlcochová, Petra; Sácha, Pavel; Hilgert, Ivan; Majer, Pavel; Slusher, Barbara S; Horejsí, Václav; Konvalinka, Jan (European journal of biochemistry, 2004)
Human glutamate carboxypeptidase II (GCPII) is a co-catalytic metallopeptidase and its putative catalytic domain is homologous to the aminopeptidases from Vibrio proteolyticus and Streptomyces griseus. In humans, the enzyme is expressed predominantly in the nervous system and the prostate. The prostate form, termed prostate-specific membrane antigen, is overexpressed in prostate cancer and is used as a diagnostic marker of the disease. Inhibition of the form of GCPII expressed in the central nervous system has been shown to protect against ischemic injury in experimental animal models. Human GCPII consists of 750 amino acids, and six individual domains were predicted to constitute the protein structure. Here, we report the analysis of the contribution of these putative domains to the structure/function of recombinant human GCPII. We cloned 13 mutants of human GCPII that are truncated or extended at one or both the N- and C-termini of the GCPII sequence. The clones were used to generate stably transfected Drosophila Schneider's cells, and the expression and carboxypeptidase activities of the individual protein products were determined. The extreme C-terminal region of human GCPII was found to be critical for the hydrolytic activity of the enzyme. The deletion of as few as 15 amino acids from the C-terminus was shown to completely abolish the enzymatic activity of GCPII. Furthermore, the GCPII carboxypeptidase activity was abrogated upon removal of more than 60 amino acid residues from the N-terminus of the protein. Overall, these results clearly show that amino acid segments at the N- and C-termini of the ectodomain of GCPII are essential for its carboxypeptidase activity and/or proper folding.
Keywords: Electrophoresis, Polyacrylamide Gel; Humans; Catalysis; sekvence nukleotidů; DNA primery; elektroforéza v polyakrylamidovém gelu; glutamátkarboxypeptidasa II; Antigens, Surface; Blotting, Western; antigeny povrchové; lidé; zvířata; aminokyseliny; Amino Acids; Protein Folding; Base Sequence; sbalování proteinů; DNA Primers; Glutamate Carboxypeptidase II; Animals; western blotting; katalýza